Relative Spatial Frequency Processing Drives Hemispheric Asymmetry in Conscious Awareness - Piazza, Elise A.; Silver, Michael A. (Frontiers in Psychology, 2017)
Visual stimuli with different spatial frequencies (SFs) are processed asymmetrically in the two cerebral hemispheres. Specifically, low SFs are processed relatively more efficiently in the right hemisphere than the left hemisphere, whereas high SFs show the opposite pattern. In this study, we ask whether these differences between the two hemispheres reflect a low-level division that is based on absolute SF values or a flexible comparison of the SFs in the visual environment at any given time. In a recent study, we showed that conscious awareness of SF information (i.e., visual perceptual selection from multiple SFs simultaneously present in the environment) differs between the two hemispheres. Building upon that result, here we employed binocular rivalry to test whether this hemispheric asymmetry is due to absolute or relative SF processing. In each trial, participants viewed a pair of rivalrous orthogonal gratings of different SFs, presented either to the left or right of central fixation, and continuously reported which grating they perceived. We found that the hemispheric asymmetry in perception is significantly influenced by relative processing of the SFs of the simultaneously presented stimuli. For example, when a medium SF grating and a higher SF grating were presented as a rivalry pair, subjects were more likely to report that they initially perceived the medium SF grating when the rivalry pair was presented in the left visual hemifield (right hemisphere), compared to the right hemifield. However, this same medium SF grating, when it was paired in rivalry with a lower SF grating, was more likely to be perceptually selected when it was in the right visual hemifield (left hemisphere). Thus, the visual system’s classification of a given SF as “low” or “high” (and therefore, which hemisphere preferentially processes that SF) depends on the other SFs that are present, demonstrating that relative SF processing contributes to hemispheric differences in visual perceptual selection.